Determinant factors of physical performance and specific throwing in handball players of different ages - Ortega-Becerra, M.; Pareja-Blanco, F.; Jiménez-Reyes, P.; Cuadrado-Penafiel, V.; González-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to analyze various fitness qualities in handball players of different ages and to determine the relationships between these parameters and throwing velocity. A total of 44 handball players participated, pooled by age groups: professional (ELITE, n = 13); under-18 (U18, n = 16); under-16 (U16, n = 15). The following tests were completed: 20-m running sprints; countermovement jumps (CMJs); jump squat to determine the load that elicited ~20 cm jump height (JSLOAD-20 cm); a progressive loading test in full squat and bench press to determine the load that elicited ~1 m/s (SQ-V1-LOAD and BP-V1-LOAD); and handball throwing (jump throw and 3-step throw). ELITE showed greater performance in almost all sprint distances, CMJ, JSLOAD-20 cm, and bench press strength than U18 and U16. The differences between U18 and U16 were unclear for these variables. ELITE also showed greater (p < 0.001) performance for squat strength and throwing than U18 and U16, and U18 attained greater performance (p = 0.05) for these variables than U16. Throwing performance correlated (p = 0.05) with sprint times (r = -0.31; -0.51) and jump ability (CMJ: r = 0.39; 0.56 and JSLOAD-20 cm: r = 0.57; 0.60). Muscle strength was also associated (p < 0.001) with both types of throw (SQ-V1-LOAD: r = 0.66; 0.76; and BP-V1-LOAD: r = 0.33; 0.70). These results indicate that handball throwing velocity is strongly associated with lower-limb strength, although upper-limb strength, jumping and sprint capacities also play a relevant role in throwing performance, suggesting the need for coaches to include proper strength programs to improve handball players' throwing velocity.